Biodegradable Composites : Materials, Manufacturing and Engineering - Davim, J. Paulo; Kumar, Kaushik (Advanced Composites ;, 2019)
With conventional materials contributing greatly to environmental waste, biodegradable and natural composites have grown in interest and display low environmental impact at low cost across a wide range of applications. This book provides an overview of different biodegradable and natural composites and focuses on efforts into increasing their mechanical performance to extend their capabilities and applications.